2014
DOI: 10.1111/1346-8138.12694
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of refractory cutaneous Rosai–Dorfman disease with vincristine

Abstract: Dear Editor, We report a patient with refractory cutaneous Rosai-Dorfman disease (RDD) who was successfully treated with vincristine. A 41-year-old man presented with a 2-year history of slowly growing erythematous nodules and plaques on the bilateral cheeks, trunk and limbs. The lesions were asymptomatic and enlarged slowly. He was treated with intralesional betamethasone, oral thalidomide, Tripterygium glycosides and isotretinoin successively over several months, which showed no effect, and new lesions conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…84 A patient with multiplyrelapsed nodal RDD responded to cytarabine/prednisone/ vincristine followed by MTX/6-MP maintenance. 85 Successful treatment of refractory cutaneous RDD was reported with singleagent vincristine 86 and low-dose MTX. 87 In addition, azathioprine and interferon-a induced long-term remissions in patients with RDD.…”
Section: Treatmentmentioning
confidence: 99%
“…84 A patient with multiplyrelapsed nodal RDD responded to cytarabine/prednisone/ vincristine followed by MTX/6-MP maintenance. 85 Successful treatment of refractory cutaneous RDD was reported with singleagent vincristine 86 and low-dose MTX. 87 In addition, azathioprine and interferon-a induced long-term remissions in patients with RDD.…”
Section: Treatmentmentioning
confidence: 99%
“…La cirugía puede ser curativa en casos unifocales, pero tiene utilidad limitada ante múltiples lesiones recurrentes (14). Algunos reportes indican beneficio con metotrexato oral en dosis bajas (15) o con vincristina como agente único (16). Otros medicamentos inmunomoduladores como talidomida (17), lenalidomida (18) o interferón (19) también han mostrado actividad; sin embargo, su perfil de toxicidad debe considerarse previo al inicio del tratamiento.…”
Section: Discussionunclassified
“…IgG4-related diseases have been considered an etiology when IgG4 + plasma cells were described in RDD lesions along with elevated serum IgG4 levels, but these have not been consistent. 5 Mutations in MAPK/ERK pathway have been document-ed in 33% of RDD patients in a retrospective study, and interestingly, the mutational profile was correlated with the location of disease -head and neck-, but not with clinical outcomes. 6 The diagnosis of RDD is heavily reliant on histology and immunohistochemistry.…”
Section: A B C Dmentioning
confidence: 99%
“…1,10,11 Extensive and systemic disease, as in this case, have been managed with a variety of largely ineffective therapies including steroids, rituximab, and cytotoxic chemotherapy with vinca alkaloids, anthracyclines, alkylating agents and antimetabolites. 2,5,9,12,13 Details of these are limited to small studies and case reports, and nothing has been shown to be of consistent long-term benefit. Most recently, a case of RDD with activating KRAS mutation was treated with targeted therapy of cobimetinib, but again with limited follow up of a radiographic response after two months.…”
mentioning
confidence: 99%